MEMBANGUN PROTOTYPE SISTEM INFORMASI ARSIP ELEKTRONIK SURAT PERJANJIAN KERJASAMA PADA BUSINESS SUPPORT DEPARTEMENT (Jurnal Pilar Nusa Mandiri, 2018)
Good and fast information is needed for every organization or company, in order to help the efficiency and effectivity of work. Nowadays, the usage of internet was so develop. Internet is used looking for information and business process support, so that encourage the company be more competitive. On the Business Support Department of Consumer Cards Group in Bank Mandiri, currently is less effective at management archives to keep the memorandum of understanding between Bank Mandiri and Partner. On the chance of could simplify these process in Business Support Department, Hopefully the system can optimize the process as well as present the internal information, such as to filing the memorandum of understanding report with computerization system based on web application, to maximize the effectiveness of works, to keep and access data quickly and efficiency. Finally, the information result will be fast and.
Keywords: Electronic Archives; E-Filing; Information Systems